Tax administration information systems concept, design, and implementation. - Tansey, David (Governance briefs.)
The benefits of upgraded ICT systems for tax authorities can include greater revenue mobilization as well as enhanced efficiency, transparency, and governance. However, the financial costs are often large and therefore require careful consideration. The brief provides valuable insights to help ensure well-informed ICT investments. It discusses ICT strategies, bespoke versus off the shelf solutions, system design, human resources required for implementation, and more.